INTRAPLATE MAGMATISM OF THE DE LONG ISLANDS: A RESPONSE TO THE PROPAGATION OF THE ULTRASLOW-SPREADING GAKKEL RIDGE INTO THE PASSIVE CONTINENTAL MARGIN IN THE LAPTEV SEA - Silantyev S.A.; Karpenko S.F.; Kostitsyn Yu.A.; Bogdanovskii O.G.; Fedorov P.I. (My University, 2004)
Synthesis of petrological, geochemical, and isotopic data on volcanic rocks and a related suite of xenoliths in the De Long Islands in the eastern sector of the Arctic basin is presented with the aim of reproducing the geochemical nature of the mantle sources of basaltic magmatism and its geodynamic environment in the continental shelf of the Laptev Sea, southeast of its intersection with the southern termination of the Gakkel Ridge. The main tool of this research was the comparative analysis of the isotopic characteristics of magmatic products on islands of this archipelago situated at different distances from the oceanic margin of the shelf. The reconstructed magmatic evolution at De Long Islands implies its close relations with the activity of a plume mantle source that occurred beneath the continental shelf of the Laptev Sea and was responsible for pulses of magmatic activity in this area of the eastern sector of the Arctic over the past 124 m.y. The volcanic activity at De Long Islands is determined to have become systematically younger from the offshore boundary of the continental shelf in the Laptev Sea (Bennett Island) inward the shelf (Zhokhov Islands) and farther southeastward (Vil'kitskii Island).
Keywords: INTRAPLATE MAGMATISM; CONTINENTAL MARGIN; GAKKEL RIDGE; LAPTEV SEA; BASALTIC MAGMATISM